Recombinant Growth hormone response in Indian girls with Turner syndrome - Inderpal Singh Kochar; Smita Ramachandran; Aashish Sethi (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2018)
Turner syndrome (TS) is characterized by short statute and ovarian dysgenesis in females with one X chromosome and partial or complete absence of the second X. It has an estimated birth prevalence of 1/2000 to 1/5000 female live births [1]. There is a global growth delay in TS characterized by slight intrauterine growth retardation, delayed growth during infancy and childhood, and lack of a pubertal growth spurt [2].